Inflammatory stimuli promote growth and invasion of pancreatic cancer cells through NF-κB pathway dependent repression of PP2Ac - Tao, Min (Cell Cycle, 2016)
Previous studies have indicated that inflammatory stimulation represses protein phosphatase 2A (PP2A), a well-known tumor suppressor. However, whether PP2A repression participates in pancreatic cancer progression has not been verified. We used lipopolysaccharide (LPS) and macrophage-conditioned medium (MCM) to establish in vitro inflammation models, and investigated whether inflammatory stimuli affect pancreatic cancer cell growth and invasion PP2A catalytic subunit (PP2Ac)-dependently. Via nude mouse models of orthotopic tumor xenografts and dibutyltin dichloride (DBTC)-induced chronic pancreatitis, we evaluated the effect of an inflammatory microenvironment on PP2Ac expression in vivo. We cloned the PP2Acα and PP2Acβ isoform promoters to investigate the PP2Ac transcriptional regulation mechanisms. MCM accelerated pancreatic cancer cell growth; MCM and LPS promoted cell invasion. DBTC promoted xenograft growth and metastasis, induced tumor-associated macrophage infiltration, promoted angiogenesis, activated the nuclear factor-κB (NF-κB) pathway, and repressed PP2Ac expression. In vitro, LPS and MCM downregulated PP2Ac mRNA and protein. PP2Acα overexpression attenuated JNK, ERK, PKC, and IKK phosphorylation, and impaired LPS/MCM-stimulated cell invasion and MCM-promoted cell growth. LPS and MCM activated the NF-κB pathway in vitro. LPS and MCM induced IKK and IκB phosphorylation, leading to p65/RelA nuclear translocation and transcriptional activation. Overexpression of the dominant negative forms of IKKα attenuated LPS and MCM downregulation of PP2Ac, suggesting inflammatory stimuli repress PP2Ac expression NF-κB pathway–dependently. Luciferase reporter gene assay verified that LPS and MCM downregulated PP2Ac transcription through an NF-κB–dependent pathway. Our study presents a new mechanism in inflammation-driven cancer progression through NF-κB pathway–dependent PP2Ac repression.